PURPOSE AND CRITERIA OF RISK DIVERSIFICATION IN COMMERCIAL BANKS - Bakhriddinov Sharofiddin (American Journals, 2024)
In the article, the goals and tasks of risk diversification in banks, the results achieved by banks through diversification, as well as the factors affecting diversification are studied in a wide scale. Opinions of economists who conducted research on this topic were studied and interpreted. At the end of the scientific work, conclusions and proposals were formed based on the knowledge learned.
Keywords: Commercial banks, globalization, risk, bank risks, credit risks, diversification, national economy, national currency, monetary policy, bank assets, bank liquidity, international financial institutions, interest rate.